Transnational studies twenty years later: a story of encounters and dis-encounters - Besserer,Federico (2018)
This article supports the argument that the researches on transnationalism and cultural studies had moments of confrontation and that, in these discussions, they influenced each other positively. I will try to expose this relationship from my own anthropological experience. The work concludes with a concern about the way in which the emergence of transnational actors is forming part of a new hegemonic formula for the functioning of political economy. Therefore, I will argue that the discussion in the researches on transnationalism and on the cultural studies should help to build a critical theory of the current moment, for which I propose five lines of work.